2013
DOI: 10.1007/s11259-013-9559-9
|View full text |Cite
|
Sign up to set email alerts
|

The immunology and genetics of resistance of sheep to Teladorsagia circumcincta

Abstract: Teladorsagia circumcincta is one of the most economically important gastrointestinal nematode parasites of sheep in cool temperate regions, to which sheep show genetically-varying resistance to infection. This is a very common parasite and viable sheep production requires the extensive use of anthelmintic drugs. However, the emergence of drug-resistant parasites has stimulated the search for alternative control strategies to curb production losses. Lambs become infected soon after weaning and begin to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 163 publications
(197 reference statements)
2
51
0
Order By: Relevance
“…Binding of IL-12 to its receptors activates the Th1 pathway and triggers the production of its transcription factors (TBX21, HLX). These in turn, promote the production of IFN-γ (Venturina et al, 2013). On the contrary, Sayers et al (2005b) supported a relationship between IFN-γ and resistance to nematode infection in Texel breed.…”
Section: The Role Of Cytokines and T Helper (Th) Cellsmentioning
confidence: 87%
See 4 more Smart Citations
“…Binding of IL-12 to its receptors activates the Th1 pathway and triggers the production of its transcription factors (TBX21, HLX). These in turn, promote the production of IFN-γ (Venturina et al, 2013). On the contrary, Sayers et al (2005b) supported a relationship between IFN-γ and resistance to nematode infection in Texel breed.…”
Section: The Role Of Cytokines and T Helper (Th) Cellsmentioning
confidence: 87%
“…Some studies on ruminants have shown constant or increased expression of IFN-γ and IL-12 despite a predominant Th2 response in H. contortus infection (Meeusen et al, 2005;Pernthaner et al, 2005). In another study, IFN-γ expression was unaffected by T. circumcincta infection of either immune or naive lambs (Craig et al, 2007;Venturina et al, 2013). Other researchers concluded that nematodes can also induce various levels of a Th1 response (Finkelman and Urban, 2001;Li et al, 2012).…”
Section: The Role Of Cytokines and T Helper (Th) Cellsmentioning
confidence: 98%
See 3 more Smart Citations